PENGARUH KEPEMIMPINAN ASTA BRATA DAN MEDIA SOSIAL TERHADAP BUDAYA DI SEKOLAH DASAR DI KECAMATAN NUSA PENIDA KABUPATEN KLUNGKUNG - Putu Meli Agustina; Basilius Redan Werang; Luh Sri Wisma Jayanti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to analyze the relationship between Asta Brata leadership and social media on school culture in elementary schools in Nusa Penida District, Klungkung Regency. This study uses a quantitative approach with an ex post facto research type. The study population was all 75 teachers in Nusa Penida District. The sampling technique used saturated sampling so that the entire population was used as a research sample. Data collection was carried out using a questionnaire with a Likert scale. Data analysis was carried out through descriptive statistical tests and hypothesis testing using Spearman Rank correlation. The results showed that Asta Brata leadership has a very strong and significant positive relationship with school culture with a correlation coefficient value of 0.826 and a significance value of 0.000 <0.05. Meanwhile, social media has a significant positive relationship but with a low level of relationship with school culture with a correlation coefficient value of 0.267 and a significance value of 0.020 <0.05. The findings of this study indicate that the application of local wisdom-based leadership values, especially Asta Brata, has an important role in building a positive school culture in elementary schools.